Tentative Reference Acts? ‘Recognitional Demonstratives’ as Means of Suggesting Mutual Knowledge – or Overriding a Lack of It - Consten, Manfred; Averintseva-Klisch, Maria (Research in Language, 2012)
In an explorative study on German oral corpus data we investigate recognitional use of proximal demonstratives as a means of explicit speaker-hearer interaction shaping the discourse structure. We show that recognitionals mark tentative reference acts in that speakers suggest - or pretend - mutual knowledge of the referent, at the same time appealing to the hearers to accept the reference. Hearers may tacitly or explicitly accept the referential act or deny it asking for clarification, in the latter case making speakers change the intended local discourse topic. On these grounds we argue against a differentiation between recognitional and indefinite demonstratives, subsuming both as kinds of recognitional use under ‘pretended’ cognitive proximity.